Civilization Analysis as a Sociology of Culture - Kavolis, Vytautas (Sociologija. Mintis ir veiksmas, 1998)
Translation: Kavolis, Vytautas. 1985. Civilization Analysis as a Sociology of Culture. Sociological Theory. 1: 29-38.